Pengetahuan dan Persepsi Politik para Pemilih Pemula: Studi Kasus pada Siswa Sekolah Menengah Atas di Kota Batam (Jurnal Bawaslu Provinsi Kepulauan Riau, 2024)
Senior high school/Vocational High School students can be categorized as first-time voter or prospective voter. Good and broad political knowledge among first-time voter is likely to increase participation in general elections. This research aims to explore how students' political knowledge penetrates them to form political knowledge and perceptions. The qualitative approach in this research was carried out to explore more vivid information through direct interviews with four high school/vocational school students. Based on the research results, it was found that students' political knowledge comes through several subjects at school such as citizenship education and Bahasa Indonesia. Extra-curricular activities such as the OSIS and Scouts, external organizations such as the KPU, parties, social media, social institutions, academics, family and friends also contribute to providing political knowledge to students. The political perceptions of first-time voter can be influenced from a series of information from various sources. This research concludes that the perceptions of first-time voter about politics and the direction of voters in regional head elections in the near future can be influenced by many factors such as learning at school, the environment, family and also social media. Students as first-time voter do not remember everything they get from various sources, but what is positive or negative will influence and color their political attitudes in the future.